Implementation of Video Feedback (FVB) Technology in Supporting Futsal Playing Skills - Oman Hadiana; Ribut Wahidi; Asep Mahpudin; Muhammad Rama Sanjaya; Ramanda Aditya Maulandani; Deliya Anitiara Rufikah (Jurnal Pengabdian Kepada Masyarakat MEMBANGUN NEGERI, 2024)
Futsal is a sport that is growing rapidly in various countries, including Indonesia. However, in the midst of the hegemony of the very dynamic development of futsal, in reality the achievements of futsal clubs that are members of the Kuningan Regency Futsal Association (AFKab Kuningan) have not been able to compete at the regional level. The partner problems that we found include the futsal playing skills of AFKab Kuningan member players still need to be improved, this is the result of observations during training and during matches. The purpose of community service activities is to implement Video Feedback (VFB) in every futsal training process to support player playing skills. The method of implementing community service activities that we carry out consists of five stages, namely socialization, training, application of technology, mentoring and evaluation, and program sustainability. Community service activities have succeeded in improving the futsal playing skills of futsal club players in the Kuningan Regency Futsal Association. The use of Video Feedback (VFB) technology has proven effective in helping players and coaches conduct direct evaluations of the game, thus facilitating improvements in technique, tactics, and overall team coordination. Through VFB, coaches can provide more specific feedback, while players can better understand their weaknesses and potential.